The Impact of School Culture on Teacher Efficacy through Teacher Leadership as an Intervening Variable in Regents Secondary School Bali - Budiarto, Yoel Agung; Tin Agustina Karnawati; Dany M. Handarini (Kelola: Jurnal Manajemen Pendidikan, 2024)
Teacher efficacy is a central aspect of education that reflects a teacher's belief in their ability to influence student learning outcomes. A conducive school culture, including commitment and collegial support, plays an important role in strengthening teachers' confidence in teaching effectively. Additionally, the role of teacher leadership in motivating and guiding is significant in improving teacher efficacy. This study aims to explore the effect of school culture on teacher efficacy through the mediation of teacher leadership. Using a saturated sample technique, this study involved 39 respondents from Regents Secondary School Bali. Data analysis using SEM (SmartPLS) showed a positive effect of school culture on teacher efficacy, but no significant effect of teacher leadership on teacher efficacy. The study also found that there was no direct effect of school culture on teacher efficacy, nor through teacher leadership. These findings emphasize the importance of a deeper understanding of the dynamics of school culture and the role of teacher leadership in strengthening teacher efficacy to sustainably improve education quality.